Komunikasi Homofili Gibran Rakabuming Raka - Yogie Alwaton (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
This research aimed to analyze the homophilous political communication used by Gibran in winning Mayor of Surakarta. The concept of homophily is used to explain the relationship between Gibran's victory and his voters in Surakarta, Central Java. By using literature study methods and data collection techniques through primary news sources and social media searches, the results showed that Gibran had implemented homophily through similarities in aspects such as speech, clothing, art and culture, as well as political party affiliation. Gibran is seen carrying out various aspects in common with his citizens in Surakarta. He has implemented homophily so that his political communication runs well. As a result, his voting base was very strong and in the end he was able to win the mayoral election and become Mayor of Surakarta.